(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1865)
A follow-up to John Grigor’s previous paper on this topic (see Vol V, pp.116-119). He describes the further excavations he performed and speculates on the structure’s use. Although he initially believed that it might have been a gravesite, the results of his excavations convinced him it was more likely a domestic dwelling.